2014
DOI: 10.4049/jimmunol.1301914
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 in Dendritic Cells Inhibits IL-12 Production and Controls Th1 Immune Responses against Leishmania major

Abstract: IRF4 is a transcription factor from the IRF factor family that plays pivotal roles in the differentiation and function of T and B lymphocytes. Although IRF4 is also expressed in dendritic cells (DCs) and macrophages, its roles in these cells in vivo are not clearly understood. In this study, conditional knockout mice that lack IRF4 in DCs or macrophages were generated and infected with Leishmania major. Mice lacking DC expression of IRF4 showed reduced footpad swelling compared with C57BL/6 mice, whereas those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 47 publications
5
30
0
Order By: Relevance
“…While a subset of CD11b + lung DCs expresses and depends on IRF4 expression as outlined above, our data show that numbers of CD11b + DCs in the dermis were not reduced by this same Irf4 deficiency. In fact, numbers of dermal CD11b + DCs were increased in CD11c-cre-Irf4 −/− mice, consistent with their inability to migrate to LN, as we and others observed previously (11, 25). While both pre-cDCs and monocytes were reported to give rise to lung and dermal CD11b + DCs, it is notable that lung CD11b + DCs were found to be much more dependent on Flt3L (29).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While a subset of CD11b + lung DCs expresses and depends on IRF4 expression as outlined above, our data show that numbers of CD11b + DCs in the dermis were not reduced by this same Irf4 deficiency. In fact, numbers of dermal CD11b + DCs were increased in CD11c-cre-Irf4 −/− mice, consistent with their inability to migrate to LN, as we and others observed previously (11, 25). While both pre-cDCs and monocytes were reported to give rise to lung and dermal CD11b + DCs, it is notable that lung CD11b + DCs were found to be much more dependent on Flt3L (29).…”
Section: Discussionsupporting
confidence: 91%
“…Mature DCs continue to express these transcription factors, which specify gene expression programs that direct their functional responses. IRF4-expressing DCs are important for the DC-driven polarization of T H 17 responses in the intestine and lung (6, 7), for the induction of T H 2 responses in lung allergy and skin parasite models (810) and for attenuation of T H 1 responses (11). In turn, IRF8-expressing DCs are often most important for T H 1 and CD8 + T cell responses, although the role of specific DC subsets is context dependent (1216).…”
Section: Introductionmentioning
confidence: 99%
“…7 This molecule, which is modulated KLF4, directly targets the gene encoding the T H 2-promoting cytokine IL-33 ( Il33 ) while inhibiting production of the T H 1-differentiating cytokine IL-12 (Fig 1, A ). 7,8 The ability for house dust mite extract to upregulate IL-33 in mouse DCs through signaling through the C-type lectin receptor Dectin-2 suggests that allergen can trigger a similar process. 9 Additional T H 2-licensing stimuli include innate cytokines secreted by epithelial cells (eg, thymic stromal lymphopoietin [TSLP], IL-25, and IL-33), as well as IL-6 and the Notch ligand Jagged1, depending on the context.…”
Section: Th2 Differentiation and T-cell Trafficking In Asthmatic Patimentioning
confidence: 99%
“…Although the exact DC subset initiating Th2 cell responses to helminths has not been formally identified yet, in the lung and in the skin, CD11b + CD172 (SIRP1a) + conventional (c)DCs that depend on the transcription factor IRF4 and KLF4 are necessary and sufficient to induce adaptive Th2-cell-associated immune responses (Akbari et al, 2014;Gao et al, 2013;Kumamoto et al, 2013;Plantinga et al, 2013;Tussiwand et al, 2015;Williams et al, 2013). The mechanisms by which these DCs induce Th2 cell immunity are poorly understood, compared with Th1, Th17, and T regulatory (Treg) cell responses, but several studies have shown the importance of the affinity of the major histocompatibility complex-T cell receptor (MHC-TCR) interaction, the tumor necrosis factor (TNF) ligand family member OX40L, the Notch ligand Jagged1, the cytokine IL-6, and the IRF4-induced absence of IL-12 production (Akbari et al, 2014;Amsen et al, 2004). Another reason why the initiation of Th2 cell immunity is so obscure is that DCs do not produce the polarizing IL-4 cytokine that drives Th2 cell immunity in many models.…”
Section: Introductionmentioning
confidence: 99%